Predictive Value of Occult Metastasis and Survival Significance of Metabolic Tumor Volume Determined by PET-CT in cT1-2N0 Squamous Cell Carcinoma of the Tongue - Yang, Lijie; Liu, Fei; Wu, Yao; Fang, Qigen; Zhang, Xiaojun; Du, Wei; Zhang, Xu; Chen, Defeng; Luo, Ruihua (Frontiers in Oncology, 2020)
Objectives: Our goal was to analyze the possibility of using metabolic tumor volume (MTV) to predict occult cervical metastasis and survival in cT1-2N0 squamous cell carcinoma (SCC) of the tongue. Methods: Data on the primary tumor MTV and cervical node status as determined by the maximum standardized uptake value were retrieved. The sensitivity and specificity in predicting occult metastasis were calculated with a fourfold table. Associations between occult metastasis and clinicopathological variables were evaluated by univariate and multivariate analyses. The main study endpoints were locoregional control (LRC) and disease-specific survival (DSS). Results: A total of 24 (20.3%) of 118 patients had occult metastasis. An MTV cutoff value of 4.3 cm3 showed a sensitivity of 50.0% and a specificity of 76.6% in predicting occult metastasis. The sensitivity and specificity of PET-CT in predicting occult metastasis in cT1 tumors were 66.6% and 89.8%, respectively, with values of 83.3% and 67.3%, respectively, when combined with the MTV. The sensitivity and specificity of PET-CT in predicting occult metastasis in cT2 tumors were 72.2% and 82.2%, respectively, with values of 88.9% and 57.8%, respectively, when combined with the MTV. Patients with MTV≥4.3 cm3 had a higher occult metastasis rate than patients with MTV<4.3 cm3. The 5-year LRC and DSS rates were 86% and 94%, respectively, in patients with MTV<4.3 cm3 and 54% and 72%, respectively, in patients with MTV≥4.3 cm3. Both differences were found to be significant in univariate and multivariate analyses. Conclusions: MTV≥4.3 cm3 was associated with an increased probability of occult metastasis and lower LRC and DSS rates in early-stage SCC of the tongue.